Implementing Data Governance with Multi-Modal Privacy-Preserving Record Linkages between Restricted and Public Open Enclaves - Gersing, Kenneth; Michael, Sam; Prior, Fred; Saltz, Joel; Moffitt, Richard; Rogovin, Sara; Phua, Jasmin; Grannis, Shaun; Amor, Ben; Girvin, Andrew; Baghal, Ahmad (International Journal of Population Data Science, 2024)
Data centralization is increasingly non-viable in the changing landscape of data privacy and data governance. New models of data sharing are needed, in particular when privacy-preserving record linkages (PPRL) are being used to connect data within restricted data enclaves and public open enclaves. We share a privacy-preserving data-sharing infrastructure that employs a linkage honest broker implementation of PPRL connecting structured electronic health record data between the National Center for Advancing Translational Science (NCATS) National Clinical Cohort Collaborative (N3C), a restricted data enclave, with the National Cancer Institute (NCI) Cancer Imaging Archive (TCIA), a public open enclave. In particular we will address: Data governance models needed when linking data from restricted vs. public enclaves Specific privacy-preserving consideration when linking to imaging data which contain specific structured data and imaging considerations Privacy-preserving data aggregation when combining multi-modal data from restricted data enclaves with publicly discoverable imaging data